Prediction of risk and multilevel program of prevention the children invalidity - Kasimova D.A. (Zien Journals, 2023)
Children's disability is a major problem today. Hundreds of thousands of disabled children need attention and support of society, social, medical and other assistance. The relevance of this issue indicates the quantitative growth of disability in childhood and adverse trends in its structure
Keywords: Child disability; risk factors for childhood disability; health care for children with disabilities